Rabbinic narrative : a documentary perspective - Neusner, Jacob, 1932-2016 (Brill reference library of Judaism, 2003)
This detailed, systematic classification of rabbinic narrative opens a road towards the documentary analysis of rabbinic narrative and fills out an important chapter in the documentary hypothesis of the rabbinic canon in the formative age.